Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Tematik Terpadu Menggunakan Model Flipped Classroom di Kelas V SDN 176/Iv Kota Jambi - Fadhilla, Khairana; Reinita, Reinita (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This research purpose to improve student learning outcomes in thematic learning using Flipped Classroom model in class V SDN 176/IV JAMBI CITY. This research is Classroom Action Research, subjects in this study are teachers and students of grade V there are 8 male students and 8 female students. The results showed an increase, : a) the results of RPP observations in first cycle 81%, in second cycle 97%. b) the results of teacher activity in first cycle are 78.5%, in second cycle 93%. c) the results of student activity in first cycle are 78.5%, in second cycle 93%.